Trypsin immobilisation on zeolites - Rocha, Cristina M. R. (2005)
This work compares different types of zeolites (NaA, NaX and NaY) as potential carriers for trypsin immobilisation. Silica was also used as a traditional carrier. Covalent attachment to the carriers was tested using glutaraldehyde. The efficiency of immobilisation and activity, operation and storage stability of free and immobilised enzyme on the three supports were studied. Optimum value of operation temperature was determined for trypsin immobilised on the best zeolite. Trypsin was most successfully immobilised on NaY by covalent attachment using glutaraldehyde. Though the best efficiencies were still obtained with silica, promising results were achieved with zeolite NaY. The ratio of immobilised protein achieved was very high, especially with silica, NaX and NaY. However there was a significant loss of enzyme activity with the immobilisation of trypsin. Optimal temperature obtained with immobilised enzyme was ca. 60 ºC, higher than the correspondent temperature for free enzyme (50 ºC).